2002
DOI: 10.1002/1615-9861(200209)2:9<1229::aid-prot1229>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Separation of human erythrocyte membrane associated proteins with one-dimensional and two-dimensional gel electrophoresis followed by identification with matrix-assisted laser desorption/ionization-time of flight mass spectrometry

Abstract: A classical proteomic analysis was used to establish a reference map of proteins associated with healthy human erythrocyte ghosts. Following osmotic lysis and differential centrifugation, ghost proteins were separated by either one-dimensional gel electrophoresis (1-DE) or two-dimensional gel electrophoresis (2-DE). Selected protein bands or spots were excised and trypsinized before mass spectrometric analyses and data mining was performed using the SWISS-PROT and NCBI nonredundant databases. A total of 102 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
93
0
7

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(106 citation statements)
references
References 23 publications
6
93
0
7
Order By: Relevance
“…They made no attempt to study RBC cytoplasmic proteins. Interestingly, two major RBC glycoproteins, glycophorin A (ϳ600,000 copies/RBC) and glycophorin C (ϳ50,000 copies/RBC) (1, 2) were not identified in the recent study (3). Glycosylated transmembrane proteins are known to be underrepresented on one-and two-dimensional gels (16), which makes the LC/MS/MS technique of great value when trying to obtain a complete proteome analysis.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…They made no attempt to study RBC cytoplasmic proteins. Interestingly, two major RBC glycoproteins, glycophorin A (ϳ600,000 copies/RBC) and glycophorin C (ϳ50,000 copies/RBC) (1, 2) were not identified in the recent study (3). Glycosylated transmembrane proteins are known to be underrepresented on one-and two-dimensional gels (16), which makes the LC/MS/MS technique of great value when trying to obtain a complete proteome analysis.…”
Section: Resultsmentioning
confidence: 98%
“…The functions of hemoglobin are also well documented. Based on four decades of study, the identity, function, and topology of many RBC membrane proteins have been determined (1)(2)(3). With the advent of modern mass spectrometry (MS) and associated proteomic techniques, determination of the RBC proteome is now plausible.…”
mentioning
confidence: 99%
“…By using multidimensional chromatographic separation followed by MS, Prx II has been identified in normal plasma; however, it could not be detected in plasma from normal health individuals by Western blot analysis (44). By using 2DE followed by MS identification, on the other hand, it could be detected in human erythrocytes (45) and follicular fluid of mature human follicles (46) but not in unfractionated plasma. Unexpectedly, in this study we found that erythrocyte breakage due to mechanical hemolysis during blood collection also contributed to the appearance of Prx II in plasma.…”
Section: Discussionmentioning
confidence: 96%
“…While working on red blood cell membrane proteins separated by SDS-PAGE and analyzed by MS, Low et al [108] were able to identify 44 polypeptides, of which only 19 were also found on 2-DE gels. The most complete study describing the proteome of red blood cells has been reported by Kakhniashvili et al [109].…”
Section: Red Blood Cellsmentioning
confidence: 99%